Immune Microenvironment: New Insight for Familial Adenomatous Polyposis - Yang, Jun; Wen, Zhengqi; Li, Wenliang; Sun, Xianghua; Ma, Junrui; She, Xueke; Zhang, Hongbin; Tu, Changling; Wang, Guoqiang; Huang, Depei; Shen, Xudong; Dong, Jian; et al. (Frontiers in Oncology, 2021)
Currently, the main treatment for familial adenomatous polyposis (FAP) is surgery, however, surgery is far from ideal as there are many complications such as uncontrollable bowel movement, pouch inflammation, anastomotic stricture and secondary fibroids. Therefore, it is necessary to further expanding the understanding of FAP and develop new treatments for FAP. The immune microenvironment including immune cells and cytokines, plays an important role in FAP and the progression of FAP to adenocarcinoma, thus may be a promising treatment for FAP. In the current review, we summary the recent progress in the immune microenvironment of FAP.